2005
DOI: 10.1152/ajpendo.00383.2004
|View full text |Cite
|
Sign up to set email alerts
|

Insulin in methionine and homocysteine kinetics in healthy humans: plasma vs. intracellular models

Abstract: -Methionine is a sulfur-containing amino acid that is reversibly converted into homocysteine. Homocysteine is an independent cardiovascular risk factor frequently associated with the insulin resistance syndrome. The effects of insulin on methionine and homocysteine kinetics in vivo are not known. Six middle-aged male volunteers were infused with L-[methyl-2 H3, 1-13 C]methionine before (for 3 h) and after (for 3 additional hours) an euglycemic hyperinsulinemic (150 mU/l) clamp. Steady-state methionine and homo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
34
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(40 citation statements)
references
References 35 publications
4
34
1
Order By: Relevance
“…In these young female rats, plasma homocysteine enrichment achieved plateau within 3 h of a primed infusion, compatible with rate constants of 1.5-1.7/h, a half-life of Ͻ30 min estimated from the observed ILR, and an assumed homocysteine content in total body water based on plasma concentration. A similar rapid equilibration (3 h) was observed in some human studies (38) but not others (19).…”
Section: Regulation Of Homocysteinemiasupporting
confidence: 83%
See 1 more Smart Citation
“…In these young female rats, plasma homocysteine enrichment achieved plateau within 3 h of a primed infusion, compatible with rate constants of 1.5-1.7/h, a half-life of Ͻ30 min estimated from the observed ILR, and an assumed homocysteine content in total body water based on plasma concentration. A similar rapid equilibration (3 h) was observed in some human studies (38) but not others (19).…”
Section: Regulation Of Homocysteinemiasupporting
confidence: 83%
“…These objectives were tackled by stable isotope procedures based on isotopomer analysis. The first involved infusion of bis-[1-13 C,methyl-2 H 3 ]methionine (36,38), whereas the second utilized [1-13 C]homocysteine in combination with [U- 13 C]methionine. The study involves virgin female rats to provide basal information before examination of changes in maternal and fetal metabolism during pregnancy in response to dietary imbalances that impact on the methionine cycle.…”
mentioning
confidence: 99%
“…In this study, the relative plasma [ 13 C]homocysteine/ [ 13 C]methionine enrichments were considerably higher than recent reports in humans under postabsorptive (37,38) and insulin-stimulated conditions. Theoretically, in tissues with the enzymatic capacity for transmethylation the intracellular enrichment of [ 13 C]methionine and [ 13 C]homocysteine should be similar, assuming that there is one common intracellular pool.…”
Section: Figcontrasting
confidence: 74%
“…Our study has showed a significant glycemia in the hyperhomocysteinemic diabetics compared to control group, suggesting possible synergistic interactions between the diabetes and the hyperhomocysteinemia. The studies linking the insulin resistance to plasma homocysteine levels are discordant [23]. Although the physiological mechanisms linking the insulin resistance to the hyperhomocysteinemia are not elucidated, it was observed that plasma homocysteine concentrations were frequently increased with the insulin resistance [23], suggesting a link between the hyperhomocysteinemia and the insulin resistance.…”
Section: Discussionmentioning
confidence: 99%
“…The studies linking the insulin resistance to plasma homocysteine levels are discordant [23]. Although the physiological mechanisms linking the insulin resistance to the hyperhomocysteinemia are not elucidated, it was observed that plasma homocysteine concentrations were frequently increased with the insulin resistance [23], suggesting a link between the hyperhomocysteinemia and the insulin resistance. The diabetes via its free radicals potentiates the deleterious effects of the hyperhomocysteinemia on the vascular endothelium [24].…”
Section: Discussionmentioning
confidence: 99%